Evaluasi Sistem Informasi Akuntansi Persediaan Barang Dalam Meningkatkan Pengendalian Internal Pada Percetakan Isma Kreasindo - Soputan Sylvia Setyani; Zahra Febriana Taufiq; Irda Agustin Kustiwi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research was conducted at Isma Kreasindo, a printing services company in Surabaya. In this research, the evaluation of the raw material inventory accounting information system uses SAS 94 as the basis for the research. From the evaluation results, it can be concluded that the internal control system and accounting information system at Isma Kreasindo have not been implemented properly. It can be seen from the dual duties between the admin section and the warehouse section. There is also a duplication of the purchasing department with the inventory control department. So there is no guarantee regarding monitoring of raw material stock in the warehouse.